Formation of effective concentration of film forming superhydrophobic coatings based on silicon dioxide - Sivolapov, Pavlo; Myronyuk, Oleksiy; Baklan, Denys; Berehovyj, Taras (Technology audit and production reserves, 2021)
The object of research is the hydrophobization of a coating based on styrene-acrylic copolymer and cellulose acetate butyrate with pyrogenic silicon dioxide. The hydrophobicity or hydrophilicity of a surface depends mainly on the chemical structure of the surface and its roughness. A relief hydrophilic surface will be wetted much more easily than a flat surface of the same material, and vice versa – an increase in the roughness of a hydrophobe is accompanied by a more pronounced repulsion of water. The size and number of irregularities significantly affect the wetting characteristics of the investigated surface. The combination of low surface energy and relief structure forms a superhydrophobic surface. Such surfaces have found application in self-cleaning, frost-resistant, antifriction, electrically conductive and oil-sorbing coatings. In this work, styrene-acrylic copolymer and cellulose acetate butyrate were used as a film former. Pyrogenic silicon dioxide Aerosil R 972, which was hydrophobized with dimethyldichlorosilane, was used as a nanofiller. In this work, the compositions were applied to laboratory glasses by dip coating. The determination of surface energy was carried out using glycerin and diiodomethane. The hydrophobic properties of the coatings were evaluated by measuring the contact angles with water using a goniometer. The analysis of the morphological structure of the coating surface with photographs of a scanning electron microscope has been carried out. The energy state of the surface of the created superhydrophobic coatings has been determined and their surface energies have been calculated using the technique based on the Owens-Wendt model. The process of hydrophobization of polymer-based coatings is investigated, which occurs both due to chemical modification with the introduction of silicon dioxide and due to the creation of nanoroughness of the surface layer of the coatings. The dependences of this process on materials are investigated using an electron microscope and the determination of their surface energy depending on the SiO2 filling. The values of the critical concentration of the modifier for the transition of polymers to the superhydrophobic state have been determined. As a result, the influence of polymer crystallinity on hydrophobization was determined by comparing changes in the surface energy of materials during their modification.